STUDENTS’ PERCEPTION ON LISTENING TO ENGLISH MONOLOGUE - Yeni, Melda (Fakultas Keguruan dan Ilmu Pendidikan, Program Studi Pendidikan Bahasa Inggris, 2017)
Perception toward a material taught in the classroom is crucial to be investigated in which it influences the result of learning. The objective of this study is to identify students’ perception of listening to English Monologue in the fifth semester of English Study Program of UNISI. This aim was achieved through a descriptive qualitative design. The sample of this research was the students in the fifth semester of English Study Program of UNISI Tembilahan. They consist of 25 students. By conducting this research, the researcher found that students’ perception of listening to English monologue in the fifth semester of English Study Program of UNSI is categorized into less level. It can be interpreted that listening to monologue is difficult. Therefore, based on this result, the researcher assumed that the students’ low result is caused by their less perception of listening to monologue.